2019
DOI: 10.1002/bit.27144
|View full text |Cite
|
Sign up to set email alerts
|

The XylR variant (R121C and P363S) releases arabinose‐induced catabolite repression on xylose fermentation and enhances coutilization of lignocellulosic sugar mixtures

Abstract: Microbial production of fuels and chemicals from lignocellulosic biomass provides a promising alternative to conventional petroleum-derived routes. However, the heterogeneous sugar composition of lignocellulose prevents efficient microbial sugar co-fermentation due to carbon catabolite repression, which negatively affects production metrics. We previously discovered that a mutant copy of the transcriptional regulator XylR (P363S and R121C; denoted as XylR*) in Escherichia coli has a higher DNA-binding affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Then a few colonies were transferred into 100 ml LB supplemented with 100 mM MOPS in 250 ml flasks without including sugars to avoid unexpected accumulation of beneficial mutations to alter glucose or xylose catabolism. These seed cultures were incubated for 12–18 h before being transferred into 300 ml AM1 media in 500 ml fermentation vessels for single sugar fermentation (Martinez et al, 2007 ) or modified AM1 media [twofold (NH 4 ) 2 HPO 4 and NH 4 H 2 PO 4 relative to the original recipe] for glucose–xylose cofermentation (Martinez et al, 2019 ). When performing cosugar fermentations, 66 g l –1 glucose and 34 g l –1 xylose were used, a typical mass ratio representative of lignocellulosic sugar compositions (Saha, 2003 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then a few colonies were transferred into 100 ml LB supplemented with 100 mM MOPS in 250 ml flasks without including sugars to avoid unexpected accumulation of beneficial mutations to alter glucose or xylose catabolism. These seed cultures were incubated for 12–18 h before being transferred into 300 ml AM1 media in 500 ml fermentation vessels for single sugar fermentation (Martinez et al, 2007 ) or modified AM1 media [twofold (NH 4 ) 2 HPO 4 and NH 4 H 2 PO 4 relative to the original recipe] for glucose–xylose cofermentation (Martinez et al, 2019 ). When performing cosugar fermentations, 66 g l –1 glucose and 34 g l –1 xylose were used, a typical mass ratio representative of lignocellulosic sugar compositions (Saha, 2003 ).…”
Section: Methodsmentioning
confidence: 99%
“…CCR results in sequential and suboptimal utilization of the secondary sugars such as xylose and arabinose, which ultimately decrease production metrics. We recently discovered that specific mutations in transcriptional regulator XylR (P363S and R121C; denoted as XylR*) releases CCR in Escherichia coli and enables coutilization of lignocellulosic sugar mixtures (Martinez et al, 2019 ; Sievert et al, 2017 ). However, besides native transcriptional regulatory mechanisms restricting xylose fermentation, there are at least two intrinsic biochemical mechanisms limiting xylose uptake and thus efficient bioconversion.…”
Section: Introductionmentioning
confidence: 99%
“…Monoculture and co-culture batch fermentations were conducted in a pH (7.0)-and temperature (37 • C)-controlled vessel containing 300 ml of modified AM1 mineral salt medium (Martinez et al, 2007;Yomano et al, 2009) containing twice the ammonium phosphate [38.8 mM (NH 4 ) 2 H 2 PO 4 and 15.1 mM (NH 4 )H 2 PO 4 ] and 67 g L −1 glucose and 33 g L −1 xylose (Flores et al, 2019;Martinez et al, 2019). pH was maintained by automatic addition of 6 M KOH for LA-producing cultures and a mixture of 6 M KOH and 3 M K 2 CO 3 (1:4 ratio by volume) for SA-producing cultures, as previously described (Grabar et al, 2006;Jantama et al, 2008).…”
Section: Cultivation Conditionsmentioning
confidence: 99%
“…Previous studies have already shown that the latency at transition from glucose to xylose is controlled by intracellular xylR availability [ 15 ]. In addition, it was reported that xylR overexpression in E. coli enabled its exponential growth in xylose and increased production of biochemicals, such as isobutanol and ethanol, in glucose/xylose mixture sugars [ 16 , 17 ]. Burkholderia sacchari , which is an industrially viable strain for the production of xylitol, xylonic acid, and PHB, was engineered with xylose-related genes that resulted in a considerable increase in growth and PHB production via xylR overexpression [ 13 ].…”
Section: Introductionmentioning
confidence: 99%